Canada’s Finest Theatre: The Sherman Grand - Goffin, Jeffrey (Theatre Research in Canada / Recherches théâtrales au Canada, 1987)
The oldest standing theatre in Calgary, The Sherman Grand Theatre was the focal point of the local theatre scene from its opening in 1912 at the peak of the first boom years in Alberta to 1937 when it was converted to a movie house. It served as a roadhouse offering international stars and touring companies as well as a venue for concerts and productions by local amateurs. Le bâtiment théâtral le plus ancien de Calgary, le Sherman Grand Theatre fut le centre de l’activité théâtrale de cette ville depuis son ouverture en 1912, au cours de la première grande vague de prospérité de l’Alberta, jusqu’en 1937, année où il fut converti en salle de cinéma. Ce théâtre accueillait longtemps les troupes internationales et les vedettes en tournée, tout en servant de foyer pour les conceris et les productions d’amateurs locaux.